Agger nasi mucocele cause nasolacrimal duct obstruction and chronic dacryocystitis: clinical profile, management and outcome. Issue 5 (24th May 2021) - Saratziotis, Athanasios; Zanotti, Claudia; Hajiioannou, Jiannis; Emanuelli, Enzo
Abstract : Epiphora is the first symptom of acquired nasolacrimal duct obstruction (NLDO), which may be due to various causes, including paranasal sinuses and tumours of the nasal cavity. A 28-year-old male patient presented chronic dacryocystitis with left-sided epiphora. Endoscopically, a bulging of the lateral nasal wall at the left-sided agger nasi area was noted. Imaging studies (CT and MRI) revealed a left-sided giant agger nasi mucocele. An endonasal endoscopic dacryocystorhinostomy (DCR) as well as opening of the agger nasi cell with mucocele removal and anterior ethmoidectomy was performed. Based on the literature, intranasal causes have very often occurred in patients with chronic dacryocystitis, but not reported as the cause of inflammation in the mucocele of agger nasi. Identification and recognition of this endonasal rare cause of NLDO-like agger nasi mucocele entity may facilitate timely intervention and can be treated successfully with a simultaneous endoscopic DCR procedure.